Investigation of Relationship between Communication in Academic Environment and Quality of Work Life among Academic Staff - Öztürk, Özden Tepeköylü; Soytürk, Mümine; Gökçe, Hüseyin (Asian Journal of Education and Training, 2019)
In this study, it is aimed to identify the relationship between the communication in academic environment and quality of work life of the academic staff who work in the field of sports sciences. Moreover, the administrational functions of each variable are studied considering the academic titles. The research is a quantitative-correlational study. The sample of the study is formed by 51 women and 114 men out of 165 academic staff who work in the field of sports sciences at various universities in Turkey. In the study, as data collection tools, ‘’Quality of Work Life Scale’’ and ‘’Communication Analysis Inventory in Academic Environment’’ are used. Data are assessed using Pearson correlation analysis, multiple linear regression analysis and t-test. It is noted with the findings that communication in academic environment (CAE) and quality of work life (QWL) have moderate and negative relations and sub-dimensions of both variables have weak, low and moderate negative relations. Also, it is indicated that CAE is a significant predictor of QWL. It’s stated that while academic staff who have administrative position perceives the CAE and its sub-dimensions positively (except for the insufficient share of scientific knowledge and sub-dimensions of faculty atmosphere), QWL gets higher scores only in sub-dimensions about relations with colleagues,work satisfaction and taking responsibility in the office. According to academic title (except for sub-dimension of individuality), there has been found no significant difference in QWL and its sub-dimensions.